Ion mobility collision cross-section atlas for known and unknown metabolite annotation in untargeted metabolomics - Zhiwei Zhou (Nature Portfolio, 2020)
Collision cross section (CCS) information can aid the annotation of unknown metabolites. Here, the authors optimize the machine-learning based prediction of metabolite CCS values and curate a 1.6 million compound CCS atlas, improving annotation accuracy and coverage for known and unknown metabolites.